DEVELOPMENT OF DIGITAL LITERACY GAME MEDIA FOR GRADE IV ELEMENTARY SCHOOL STUDENTS - Ana Khalimatul Muna; Murbangun Nuswowati; Deby Luriawati Naryatmojo (Universitas Majalengka, 2023)
Low interest in reading affects the quality of education so that tools in the form of learning media are needed to increase students' reading interest which is relatively low due to the impact of the rise of online entertainment and games. The purpose of this research is to develop digital game media in increasing the reading interest of grade 4 elementary school students. From these problems, researchers developed a digital literacy game media in the form of developing a word guessing game application equipped with energy-saving themed reading materials to increase students' reading interest. The development of this game media not only focuses on students' reading interests but also insight into energy-saving knowledge around. This research uses the type of Research and Development (R&D) research according to Borg and Gall. Data analysis techniques carried out include preliminary studies, product development, validity tests and conclusions. From the results of the material expert validity test, it showed a score of 88% in the very high category and the validation results by media experts obtained a score of 85.6% in the very high category. So that the results show that digital literacy game media is qualified and suitable for use. Rendahnya minat baca mempengaruhi mutu pendidikan sehingga diperlukan alat bantu berupa media pembelajaran untuk meningkatkan minat baca siswa yang tergolong rendah akibat dampak dari maraknya jenis hiburan dan game online. Tujuan dilakukan penelitian ini yakni untuk mengembangkan media permainan digital dalam meningkatkan minat baca siswa kelas 4 Sekolah dasar. Dari permasalahan tersebut peneliti mengembangkan sebuah media permainan literasi digital berupa pengembangan aplikasi permainan tebak kata yang dilengkapi bahan bacaan bertema hemat energi untuk meningkatkan minat baca siswa. Pengembangan media permainan ini bukan hanya fokus pada minat baca siswa tetapi juga wawasan terhadap pengetahuan hemat energi disekitar. Penelitian ini menggunakan jenis penelitian Research and Development (R&D) menurut Borg and Gall. Teknik analisis data yang dilakukan meliputi studi pendahuluan, pengembangan produk, uji validitas dan penarikan kesimpulan. Dari hasil uji validitas ahli materi menunjukan skor 88% dalam kategori sangat tinggi dan hasil validasi oleh ahli media diperoleh skor 85,6% dalam kategori sangat tinggi. Sehingga dari hasil tersebut menunjukan bahwa media permainan literasi digital memenuhi syarat dan layak untuk digunakan.